1976
DOI: 10.1159/000144676
|View full text |Cite
|
Sign up to set email alerts
|

Die Feinstruktur des Epithels des Ductus pancreaticus major des Schafes

Abstract: Light- and electron-microscopic and some histochemical investigations on the epithelium of the ductus pancreaticus major were carried out in sheep. At least six different cell types are recognizable: (1) nondifferentiated duct cells; (2) cells containing apical secretory granules; (3) goblet cells; the mucosubstances of type 2 and 3 are PAS- and Alcian-blue-positive, also reacting with methenamine silver; (4) ciliated cells, containing a single cilium with the microtubular pattern 9 + 2; (5) tuft cells with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…In addition to brush cells and principal cells (Githens et al 1980(Githens et al , 1981(Githens et al , 1987Hubchak et al 1990), the simple epithelium of the pancreatic duct has been reported to contain different types of endocrine cells (Bendayan 1987;Lee 1988;Park and Bendayan 1992). Unlike endocrine cells, brush cells do not contain any secretory vesicles (Weyrauch and Schnorr 1976;Luciano et al 1981; our own unpublished observations) and, thus, have to be regarded as a distinct cell type that is not related to classic enteroendocrine cells of the gut. This view is further supported by the non-reactivity of brush cells with two different marker molecules of enteroendocrine cells, serotonin and chromogranin A (this study; .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition to brush cells and principal cells (Githens et al 1980(Githens et al , 1981(Githens et al , 1987Hubchak et al 1990), the simple epithelium of the pancreatic duct has been reported to contain different types of endocrine cells (Bendayan 1987;Lee 1988;Park and Bendayan 1992). Unlike endocrine cells, brush cells do not contain any secretory vesicles (Weyrauch and Schnorr 1976;Luciano et al 1981; our own unpublished observations) and, thus, have to be regarded as a distinct cell type that is not related to classic enteroendocrine cells of the gut. This view is further supported by the non-reactivity of brush cells with two different marker molecules of enteroendocrine cells, serotonin and chromogranin A (this study; .…”
Section: Discussionmentioning
confidence: 80%
“…Brush cells of the alimentary tract do not show any direct synaptic contacts with nerve fibers (Weyrauch and Schnorr 1976;Wattel and Greuze 1978;Trier et al 1987;Luciano and Reale 1990). This observation opened the question of how these cells may communicate with other cells.…”
Section: Possible Targets Of Brush Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, they have been detected in a variety of mammals in lung (Meyrick & Reid, 1968), gastrointestinal (GI) tract (Luciano et al. 1968a,b), including gallbladder (where they are particularly abundant) (Luciano & Reale, 1969), pancreas (Weyrauch & Schnorr, 1976), parotid and submandibular gland (Sato & Miyoshi, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Tuft cells, also termed brush, fibrovesicular, multivesicular, and caveolated cells by various authors, were described in the mouse stomach and duodenum (Jarvi and Keyrilainen, 1955) and rat trachea (Rhodin and Dalhamn, 1956) over 30 years ago. These distinctive cells have now been observed in a variety of mammals in most columnar epithelia derived from endoderm including stomach (Jarvi and Keyrilainen, 1955;Isomaki, 1973;Nabeyama and Leblond, 1974;Wattel and Geuze, 1978), small and large intestine (Silva, 1966;Isomaki, 1973;Nabeyama and Leblond, 1974;Tsubouchi and Leblond, 1979), biliary tract Luciano and Reale, 1979;Luciano et al, 1981), pancreatic duct ( Weyrauch and Schnorr, 1976), and respiratory tract (Rhodin and Dalhamn, 1956;Meyrick and Reid, 1968;Allan, 1978). Moreover, their recent description in the intestine of the bullfrog tadpole (Sugimoto et al, 1983) suggests that they may well be conserved during evolution.…”
mentioning
confidence: 94%